Assessing the Content of Online Agricultural Awareness Campaigns - Joy N. Rumble; Quisto Settle; Tracy Irani (Journal of Applied Communications, 2016)
This study explored the content of online agricultural awareness webpages. Content analysis was used to determine the content, image categories, messaging appeals, and frames used. The majority of the pages included images and logos, but they were less likely to include other media components, such as social media plugins. The most prevalent image types were non-farming adults, positive food products, fields, and free-roaming animals, though they were included in less than one-third of the pages. The use of non-farming adult images is likely connecting to a consumer audience, while the images of positive food products, fields, and free-roaming animals are likely providing contextual, cultural, or direct meaning to the viewers. Logical appeals were more prevalent than emotional appeals. The primary use of logical appeals could be limiting webpage effectiveness because emotional appeals are known to create stronger connections with audiences and be remembered. The most prevalent frames were agricultural education and economic. Previous literature indicates that education-only communication is traditionally less effective as consumers consider more than facts when making decisions. It is recommended that agricultural communicators pre-test webpages with target audiences prior to launch, utilize webpage planning to better reach target audiences, and conduct formative evaluations of webpages to assess effectiveness and make any needed adjustments. Additionally, it is recommended that agricultural communicators incorporate more emotional appeals into their communication messages. Future research should continue to assess online agricultural awareness information as well as the impact the information has on a consumer audience.
Keywords: Agricultural Awareness Campaigns; Agenda Setting; Content Analysis; Framing; Messaging Appeals